ETHICS AND PATHOLOGY IN THE POLISH POLICE – PROFESSIONAL AND POLITICAL ASPECTS - Ryszard Bełdzikowski (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
Based on political changes initiated in 1989 and on moral and legal patterns stipulated in the Act on the Police of 6 April 1990, this paper brings closer the development of the Police Forces in Poland up to the present day. The analysis is carried out in the context of criminal behaviour and other shameful acts performed by police officers. Most of them generally discredited the professionalism and fundamental ethical principles of the Police. However, at the same time, the Police regularly receives new legal instruments such as "the crown witness" and the so called "small crown witness" to fight organized crime, and a number of specialized structures such as the Central Investigation Bureau. The Police is systematically developing contacts and cooperation with foreign institutions such as Europol, FBI or BKA. Unfortunately, around 2003 and 2004 internal criminal activities conducted by police officers started to intensify. Corruption spread among officers of all ranks, from local police stations to the General Head Quarters. The media are full of stories of lame investigations for example in murder of the Chief of the National Police Marek Papała or murder of a young businessman Krzysztof Olewnik. Cardinal professional errors committed during these investigations put the Police in an unfavourable light. Therefore, doubts regarding professionalism, ethical values and authority of the Police seem to be justified. The author also points to reckless development of relations between the Police Head Quarters and politicians who put the Police officers of the highest rank under their dubious supervision and command. The moral values and political neutrality so important for the founding fathers of the modern Police, now after 26 years, remain a mere theoretical legal record. As a conclusion, this paper suggests a consensus solution: an institution with high public authority for example the Ombudsman or the Supreme Bar Council, in order to establish a permanent practice of appointment of the head of the Police for a 5-year term of office with the possibility of renewal for the next 5 years.